Acellular Collagen Scaffold With Basic Fibroblast Growth Factor for Repair of Traumatic Tympanic Membrane Perforation in a Rat Model. (14th July 2020) - Yao, Xu; Teh, Bing Mei; Li, Huan; Hu, Yi; Huang, Juntao; Lv, Cuiting; Bu, Shizhong; Zheng, Minghao; Shen, Yi
Abstract : Objective: To evaluate the efficacy of acellular collagen scaffold (ACS) in combination with basic fibroblast growth factor (bFGF) for the repair of traumatic tympanic membrane (TM) perforation in a rat model. Study Design: A prospective controlled animal study in a rat model of traumatic TM perforation. Setting: Tertiary medical center. Subjects and Methods: Sprague‐Dawley rats (N = 84) with unilateral traumatic perforation of the right TMs were randomized to receive ACS, bFGF, ACS in combination with bFGF (ACS/bFGF), or nothing (spontaneous healing without any interventions as a control group). The healing outcomes were evaluated by otoscopy, optical coherence tomography, histology, and transmission electron microscopy at 1, 2, and 4 weeks postoperatively. The hearing outcomes were assessed with auditory brainstem response testing. Results: ACS/bFGF resulted in higher perforation closure rates at an earlier stage than spontaneous healing, ACS, and bFGF. Based on histology, optical coherence tomography, and transmission electron microscopy, a trilaminar structure and uniform thickness with mature, densely packed collagen fibers were seen in the ACS/bFGF group. Auditory brainstem response evaluation also showed that ACS/bFGF treatment promoted faster functional hearing recovery as compared with the control group. Conclusions: ACS is an effective TM scaffold and a carrier for bFGF. ACS/bFGF improves the TM closure rate, results in better‐reconstructed TMs, and improves hearing. ACS/bFGF serves as a potential substitute for TM perforations in clinical settings.